2015
DOI: 10.1177/2168479015572372
|View full text |Cite
|
Sign up to set email alerts
|

Confounding Issues in Cancer Progress—The Impact of Investor Requirements on Senior Management Compensation and Regulatory Decisions: Tivozanib and Aveo Pharmaceuticals

Abstract: Previous research has demonstrated that profits are a key requirement in private pharmaceutical development. We sought to examine the extent that pressure of financial incentives exerted by investors and the board of directors, including senior management financial rewards, have on regulatory decisions made by senior management. Our selected case study involved Aveo Pharmaceuticals Inc (Aveo). The specific question was to what extent the terms of financing, particularly the corporate governance goals which det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Adhesion and invasion are essential during the process of lung cancer cell metastasis ( 15 , 26 ). The development of metastasis is the primary cause of the low survival rates in patients with cancer ( 27 , 28 ). In the present study, THSG was demonstrated to significantly inhibit lung cancer cell viability, adhesion and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion and invasion are essential during the process of lung cancer cell metastasis ( 15 , 26 ). The development of metastasis is the primary cause of the low survival rates in patients with cancer ( 27 , 28 ). In the present study, THSG was demonstrated to significantly inhibit lung cancer cell viability, adhesion and invasion.…”
Section: Discussionmentioning
confidence: 99%